Exclusion of women and organisational characteristics: Swedish mutual health insurance 1901–1910. Issue 8 (17th November 2019) - Andersson, Lars-Fredrik; Eriksson, Liselotte
Abstract: Mutual societies have been recognised for their ability to mitigate information asymmetry. Although successful in reducing sickness claims, the exclusion of women was common. Health insurance societies argued the exclusion was a means to reduce adverse selection and moral hazard since women were regarded as higher risk. In this paper, we explore differences in organisational characteristics between societies that excluded and societies that did not exclude women as members between 1901 to 1910. Based on panel data, the study shows that societies that excluded women were less successful in keeping down sickness claims, in relation to benefits, than gender-mixed societies.